Development of Cd3(PO4)2/rGO Coupled Semiconductor System for Effective Mineralization of Basic Violet 10 (BV 10) under UV-A Light. (2019) - Rajasri, S.; Krishnakumar, B.; Sobral, Abilio J.F.N.; Balachandran, S.; Swaminathan, M.; Muthuvel, I.
Abstract: Initially, novel Cd3 (PO4 )2 was prepared via precipitation method. It was loaded with different concentration of rGO to form rGO/CdP composites. The prepared rGO/CdP were used to degrade Basic Violet 10 (BV 10) dye under UV-A light irradiation. The optimized rGO/CdP composite was characterized along with pristine CdP and rGO by XRD, FT-IR, FT-Raman, BET, HR-SEM with EDX, HR-TEM, and UV-DRS analysis. The effect of initial dye pH in the degradation was studied. The coupled semiconductor system enhanced the photocatalytic activity and used for multiple runs, due to its remarkable stability.